Synchronized Inhibition of the Phospholipid Mediated Autoactivation of Factor XII in Plasma by β2-glycoprotein I and Anti-β2-glycoprotein I - Schousboe, Inger; Rasmussen, Margit Søe (Thrombosis and Haemostasis, 1995)
Lupus anticoagulants are a group of antibodies commonly found in patients with autoimmune diseases such as systemic lupus erythematosus. Lupus anticoagulants inhibit phospholipid dependent coagulation and may bind to negatively charged phospholipids. Recent studies have suggested an association between anti-β2-glycoprotein I and a lupus anticoagulant, whose activity is frequently dependent on the presence of β2-glycoprotein I. Based on these observations, the effect of anti-β2-glycoprotein I on the autoactivation of factor XII in plasma was investigated. Autoactivation initiated by the presence of negatively charged phospholipids, but not by sulfatide, was strongly inhibited by immunoaffinity purified anti-β2-glycoprotein I. The dose-response curve of anti-β2-gly coprotein I was identical with that of a precipitating antibody, showing no inhibition at low and high antibody dilutions and maximal inhibition at an intermediate dilution. At high antibody concentrations, an increased rate of factor Xlla activation was observed. This increase was of the same magnitude as the decreased rate observed in plasma supplemented with the same amount of β2-glycoprotein I as in the plasma itself. This confirms the inhibitory effect of β2-GP-I on the contact activation and shows that inhibition is effective on the autoactivation of factor XII in plasma. The inhibitory action of β2-glycoprotein I was independent of the inhibition caused by the anti- β2-glycoprotein I/β2-glycoprotein I complex suggesting a synchronized inhibition of factor XII autoactivation by β2-glycoprotein I and anti-β2-gly coprotein I. The inhibition caused by the antibody is suggested to be caused by a reduced availability of negatively charged phospholipids due to the binding of the anti-β2- GP-I/β2-GP-I complex. This complex may be a lupus anticoagulant.